Accountability in the public health care systems: A developing economy perspective - Lasuli Bakalikwira; Juma Bananuka; Twaha Kaawaase Kigongo; Doreen Musimenta; Veronica Mukyala (Cogent Business & Management, 2017)
The purpose of this paper is to report the results of the study carried out to examine the effects of hospital board governance and managerial competencies on accountability in the health care systems in Uganda. This study is cross–sectional and correlational. This study utilizes multiple regression models based on a sample of 52 government hospitals. The study's unit of inquiry is hospital directors and accountants. The correlation results indicate a significant positive relationship between managerial competencies and accountability. The study further finds that board governance is not significantly correlated with accountability of government hospitals. In terms of hospital governance dimensions; board composition is positively and significantly related with accountability unlike board structure and board independence. The measurements used in all the predictor variables may not perfectly represent all the dimensions although they have been defined as precisely as possible by drawing upon relevant literature. Therefore, further research on other factors that explain the variance in accountability in the health sector is needed. Whereas hitherto, corporate governance and managerial competencies had been viewed as possible explanations of accountability in the public healthcare systems, this study only confirms managerial competencies to be a significant predictor of accountability in the public healthcare systems unlike board governance.
Keywords: 650